Strategies to improve communication between the Dentist and the adolescent patient: integrative literature review (Research, Society and Development, 2021)
This study aimed to identify and describe strategies to improve communication between the dentist and adolescent patients. An integrative literature review was carried out in the MEDLINE/PubMed database using the following descriptors: adolescent, child, communication, health communication, and dentist. Retrieved studies were screened independently by two reviewers. This review included original studies with participants aged 10 to 19 years. Titles and abstracts were read first, followed by a full-text analysis for data extraction. A total of six studies were included, which covered the literature published in the last eight years. One study had a cross-sectional design, and the others were randomized controlled trials. Verbal, written and virtual communication strategies were described, such as printed brochures, mental maps, forms, and digital resources. Positive outcomes were observed concerning the reduction of pain and dental anxiety as well as greater retention of the information provided by the dentist. To conclude, dentists should make use of additional means to improve their communication with adolescent patients. Our review describes current evidence indicating that some tools are effective for this purpose and may be useful, for instance, in the care of patients with dental anxiety.